Hepatoprotective Activity of Methanolic Extract of Bauhinia purpurea Leaves against Paracetamol-Induced Hepatic Damage in Rats. (18th June 2013) - Yahya, F.; Mamat, S. S.; Kamarolzaman, M. F. F.; Seyedan, A. A.; Jakius, K. F.; Mahmood, N. D.; Shahril, M. S.; Suhaili, Z.; Mohtarrudin, N.; Susanti, D.; Somchit, M. N.; Teh, L. K.; et al.
Abstract : In an attempt to further establish the pharmacological properties of Bauhinia purpurea (Fabaceae), hepatoprotective potential of methanol extract of B. purpurea leaves (MEBP) was investigated using the paracetamol- (PCM-) induced liver toxicity in rats. Five groups of rats (n = 6 ) were used and administered orally once daily with 10% DMSO (negative control), 200 mg/kg silymarin (positive control), or MEBP (50, 250, and 500 mg/kg) for 7 days, followed by the hepatotoxicity induction using paracetamol (PCM). The blood samples and livers were collected and subjected to biochemical and microscopical analysis. The extract was also subjected to antioxidant study using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay with the total phenolic content (TPC) also determined. From the histological observation, lymphocyte infiltration and marked necrosis were observed in PCM-treated groups (negative control), whereas maintenance of the normal hepatic structural was observed in group pretreated with silymarin and MEBP. Hepatotoxic rats pretreated with silymarin or MEBP exhibited significant decrease (P < 0.05 ) in ALT and AST enzyme level. Moreover, the extract also exhibited antioxidant activity and contained high TPC. In conclusion, MEBP exerts potential hepatoprotective activity that could be partly attributed to its antioxidant activity and high phenolic content and thus warrants further investigation.